1982
DOI: 10.1111/j.1752-1688.1982.tb04536.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of SCS Models to Curve Number Variation1

Abstract: The Soil Conservation Service (SCS) models, including the TR‐20 computer program and the simplified methods in TR‐55, are widely used in hydrologic design. The runoff curve number (CN), which is an important input parameter to SCS models, is defined in terms of land use tretments, hydrologic, condition, antecedent soil moisture, and soil type. The objective of this study was to evaluate the sensitivity of the SCS models to errors in CN estimates. The results show that the effects of CN variation decrease as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 3 publications
0
28
0
2
Order By: Relevance
“…Various researchers (e.g. Bondelid et al 1982;McCuen et al 1984;McCuen 2009) demonstrated that as much as 75% of the total error in estimates of peak discharge could be ascribed to errors in the estimation of time parameters. Gericke and Smithers (2014) showed that the underestimation of time parameters by 80% or more could result in the overestimation of peak discharges of up to 200%, while the overestimation of time parameters beyond 800% could result in maximum peak discharge underestimations of up to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers (e.g. Bondelid et al 1982;McCuen et al 1984;McCuen 2009) demonstrated that as much as 75% of the total error in estimates of peak discharge could be ascribed to errors in the estimation of time parameters. Gericke and Smithers (2014) showed that the underestimation of time parameters by 80% or more could result in the overestimation of peak discharges of up to 200%, while the overestimation of time parameters beyond 800% could result in maximum peak discharge underestimations of up to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the resulting peak discharges will be overestimated by between 30% and 50% (McCuen 2009). Bondelid et al (1982) indicated that as much as 75% of the total error in peak discharge estimates could be ascribed to errors in the estimation of time parameters. In addition, McCuen (2005) highlighted that there is, in general, no single time parameter estimation method that is superior to all other methods under the wide variety of climatological, geomorphological and hydrological response characteristics that are encountered in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Według Bondelid i in. [4] błędnie oszacowane parametry związane z czasem reakcji zlewni mogą generować nawet 75%-owy błąd w wartości przepływu w kulminacji. Dlatego czas koncentracji należy szacować porównując różne metody i wybierając wartość optymalną w zależności od charakterystyki zlewni.…”
Section: Rys 1 Graficzna Interpretacja Zależności Odpływu Od Czasu unclassified